Role of Zinc in Pediatric diseases: Evidence based Guidelines - D Sharad Gedam (International Journal of Medical Research and Review, 2013)
Role of zinc in human health including growth, development, immune status and acute diarrhea is indisputable. Zinc deficiency is well known because of poor dietary habits, increased secretion and poor absorption of zinc during diarrhea. Present review will demonstrate role of zinc in various pediatric disorders and newer update. We have tried to include recent review on role of zinc in childhood diseases as per evidences available on electronic databases.